Polyhydroxyalkanoate Production by Antarctic Soil Bacteria Isolated from Casey Station and Signy Island - Goh, Y.S.; Tan, I.K.P. (2012)
Polyhydroxyalkanoate (PHA) is a family of biopolymers produced by some bacteria and is accumulated intracellularly as carbon and energy storage material. Fifteen PHA-producing bacterial strains were identified from bacteria isolated from Antarctic soils collected around Casey Station (66 degrees 17'S, 110 degrees 32'E) and Signy Island (60 degrees 45'S, 45 degrees 36W). Screening for PHA production was carried out by incubating the isolates in PHA production medium supplemented with 0.5 (w/v) sodium octanoate or glucose. 16S rRNA gene sequence analysis revealed that the isolated PHA-producing strains were mainly Pseudomonas spp. and a few were Janthinobacterium spp. All the isolated Pseudomonas strains were able to produce medium-chain-length (mcl) PHA using fatty acids as carbon source, while some could also produce mcl-PHA by using glucose. The Janthinobacterium strains could only utilize glucose to produce polyhydroxybutyrate (PHB). A Pseudomonas isolate, UMAB-40, accumulated PHA up to 48 cell dry mass when utilizing fatty acids as carbon source. This high accumulation occurred at between 5 degrees C and 20 degrees C, then decreased with increasing temperatures. Highly unsaturated mcl-PHA was produced by UMAB-40 from glucose. Such characteristics may be associated with the ability of UMAB-40 to survive in the cold. (C)2011 Elsevier GmbH. All rights reserved.